Deaths at home during COVID-19 in Scotland: Demographics, multimorbidity, and palliative care needs in population data - Savinc, Jan; Atherton, Iain (International journal of population data science, 2025)
IntroductionDeaths at home increased by a third in Scotland during the pandemic period, yet little is known about the population who died at home. Policy towards supporting this increased number will benefit from understanding differences in the socio-demographic composition and clinical needs of those dying at home following the pandemic. ObjectivesTo describe the population who died at home in Scotland during the first year of the Covid-19 pandemic and compare them to the population of decedents five years prior, in terms of demographic and clinical characteristics and estimated palliative care needs. Demographic characteristics included age, sex assigned at birth, marital status, the area-based Scottish Index of Multiple Deprivation (SIMD) and the Scottish urban-rural indicator. MethodsRetrospective cohort study of death registrations for Scottish decedents between March 2015 and March 2021, with the 12-month period from 2020-03-23 defined as the pandemic period. Death registrations were linked to 10 years of inpatient admissions to identify comorbid conditions and compute the Elixhauser Comorbidity Index (EI). Palliative care needs were estimated from underlying and contributory causes of death using ICD-10 codes. Number of distinct medications dispensed in the final 12 months of life was computed from prescribing records. A binary logistic regression model was used to estimate the association between individual characteristics, the pandemic period, and death at home, and their average marginal effects (AME). ResultsDuring the pandemic, home decedents were on average 1.03 years older, more likely to be male and married, their Elixhauser Morbidity increased by 0.39, and they received 0.25 more medication types. The EI of home decedents increased past that of care home decedents. The adjusted effect of the pandemic on probability of death at home was AME = 5.9% (95%CI 5.5%,6.3%). ConclusionsIn addition to increasing by a third, home decedents were as ill as before the pandemic or more, and were somewhat more similar to hospital and care home decedents than before the pandemic. Policy support is needed for enabling care at home for complex needs and increased support for carers.